Identifikasi Kandungan Fe Pada Pasir Besi Alam Di Kota Mataram - Susilawati Susilawati; Aris Doyan; Muhammad Taufik; Wahyudi Wahyudi; Erin R Gunawan; Kosim Kosim; Annisa Fitriani; Husniatul Khair (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
The research on coastal sand in Mataram-Lombok city, located at several beaches, namely, Gading, Loang Baloq, Penghulu Agung, and Ampenan, is to determine the percentage of magnetic mineral content, metal content, and oxide mineral composition contained on those sand. Iron is a sediment containing magnetite (Fe3O4), maghemit (ÃÂ³-Fe2O3) and hematite (ÃÂ±-Fe2O3) as the main mineral and several other minerals as a supporting mineral. Magnetic separation of natural sand by using a permanent magnet successfully separates the magnetic parts (iron sand) and non-magnetic. The separation results were then analyzed for Fe metal content, the quantity of metal content, and the quantity of oxide minerals using AAS, XRD, and XRF. The result of AAS analysis showed that Fe content in natural sand in Gading , Loang Baloq , Penghulu AgungÃÂ  and Ampenan Beach were 10,573 mg / gr, 12,816 mg / gr, 15,019 mg / gr, and 16,277 mg / gr, respectively. XRF analysis results in four locations have iron content respectively of 73.4%, 62.1%, 76.8%, and 69.8% in Hematite compound phase. As for the results of XRD analysis at these four locations the phases are magnetite and hematite phases.